MANAJEMEN KERJASAMA LEMBAGA PENDIDIKAN ISLAM DENGAN MASYARAKAT (Studi Kasus Pondok Pesantren Alam Internasional Saung Balong al-Barokah Cisambeng Palasah Majalengka) - Asep Kurniawan (LP2M IAIN Syekh Nurjati Cirebon, 2014)
Pesantren should not only concentrate on developing religious education only, but also must be concerned local economy. This concern is a manifestation of partnership management between pesantren and community. In fact, many Pesantrens are not able to play such a role in an integrated way. This study aimed to find partnership management patterns in Pesantren Alam Internasional Saung Balong al-Barokah and the community in the context of management education in economics and education. The research method was qualitative. Instruments of collecting data were an interview, unstructured observation, and documentation. Data validation was done through credibility, transferability, dependability and conformability. Techniques of data analysis were done by collecting the data, reducing data, displaying data, and concluding data. Researcher found that Pesantren Alam Internasional Saung Balong al-Barokah successfully worked together in harmony with the community in economic empowerment and education in an integrated way, so could provide the benefits. These findings should be emulated by other pesantren.